Penerapan Metode EDAS Dan Pembobotan ROC Rekomendasi Susu Formula Untuk Bayi Alergi Susu Sapi - Naomi Labora Saragi; Rico Albert Andika Saragih; Afri Nirmalasari Halawa; Efori Bu'ulolo (STMIK Budi Darma, 2022)
Breast milk is the main source of nutrition for babies before they can digest solid food. Several formula milks that contain soy or soy, honey, multivitamins, zinc and are also lactose-free can be substitutes or other alternatives for formulas containing cow's milk. In determining the best formula milk for babies allergic to cow's milk, several criteria are needed, such as Certificates and Permits, Content, Dosage (mg), Age of Baby, Price Per Package. The large number of allergic milk circulating makes people confused about which milk is suitable for children allergic to cow's milk. The best formula for babies allergic to cow's milk is A2 Enfa mil A+ Gentle Care with a value of -0.047 as the best alternative.